Integrating Decentralized Strategy Making and Strategic Planning Processes in Dynamic Environments - Andersen, Torben Juul (Journal of Management Studies, 2004)
abstract Decentralized post‐bureaucratic organizations are deemed to display superior performance in dynamic environments, but recent evidence indicates that centralized integrative cross‐functional processes may be equally critical. Accordingly, this paper hypothesizes that organizational performance can be ascribed to the simultaneous emphasis on decentralized strategy making and strategic planning processes. This is investigated in a study of 185 manufacturing organizations operating in diverse industries spanning food processing and computer products. The study shows that both decentralized decision structure and planning activities are associated with higher performance in dynamic environments. These findings confirm that effective organizations engage in more complex strategy formation processes that complement the decentralized post‐bureaucratic form with formal mechanisms of rational analyses and operational integration. The paper highlights a need to extend our understanding of the duality between decentralization and planning.